Figure dello spaesamento e dell’erranza - Colonnello, Pio (Bollettino Filosofico, 2019)
The text provides an overview of the semantic-conceptual constellation of disorientation and wandering starting from Heidegger. After a reconstruction and discussion of the critical literature most immediately relevant for the topic at stake, the reflection extends to the existential-political dimension of wandering, with a series of references to Kant, Arendt and the Greek, Roman and Jewish cultural universes. The dialogue with Heidegger, however, always underlies these argumentative passages, and is taken up again in the conclusions. Keywords: Disorientation, Absence of Homeland, Extraneousness, Forgetfulness of Being, Wanderung